Hand hygiene compliance : is there a theory-practice-ethics gap? - Mortell, Manfred (Mark Allen Publishing, 2012)
Practice is usually based on tradition, rituals and outdated information; there is often an additional gap between theoretical knowledge and its application in practice. This theory-practice gap has long existed (Allmark, 1995; Hewison et al, 1996). It often arises when theory is ignored because it is seen as idealistic and impractical, even if it is practical and beneficial. Most research relating to the lack of integration between theory and practice has concluded that environmental factors are responsible and will affect learning and practice outcomes. The author believes an additional dimension of ethics is required to bridge the gap between theory and practice. This would be a moral obligation to ensure theory and practice are integrated. To implement new practices effectively, healthcare practitioners must deem these practices worth while and relevant to their role. This introduces a new concept that the author calls the theory-practice-ethics gap. This theory-practice-ethics gap must be considered when examining some of the unacceptable outcomes in healthcare practice (Mortell, 2009). The literature suggests that there is a crisis of ethics where theory and practice integrate, and practitioners are failing to fulfil their duty as providers of healthcare and as patient advocates. This article examines the theory-practice-ethics gap when applied to hand hygiene. Non-compliance exists in hand hygiene among practitioners, which may increase patient mortality and morbidity rates, and raise healthcare costs. Infection prevention and control programmes to improve hand hygiene among staff include: ongoing education and training; easy access to facilities such as wash basins; antiseptic/alcohol handgels that are convenient, effective, and skin- and userfriendly; and organisational recognition and support for clinicians in hand washing and handgel practices. Yet these all appear to have failed to achieve the required and desired compliance in hand hygiene.